IMPLEMENTASI KEBIJAKAN DANA ALOKASI KHUSUS PENDIDIKAN PADA DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN SIGI - Fitriani, Fitriani (Katalogis, 2018)
This research intends to describe and to analyze the inhibiting and driving factors of Sigi Regency government in the policy implementation of distinctive education allocation fund. Method used is descriptive qualitative where the informant were taken through purposive sampling. Data were collected through interview, observation, and document review related to the policy implementation of distinctive education allocation fund. The process of data analysis covered data reduction, data presentation, and conclusion. The result of this research revealed that the inhibiting and driving factor determined by the content of the policy, the form of the policy, and the reputation ofactor. Financial resources are the concern of the policy indicators being implemented, in addition to the policy benefits which with the assistance of DAK in the education sector can accelerate the distribution of education in Sigi Regency particularly in the difficult territory, as well as the involvement of public where the involvement of society and committee in the school is a part of society.Â  The form indicator policy can be seen through Self-managed form of P2S (The organizing committee at the school) in the implementation of distinctive education allocation fund. The reputation of actor becomes the inhibiting factor because the human resources that needs to be improved.Â